LEVELS OF RISK OF SOIL DEFLATION - Мухаммад Исматуллаевич Умаров; Низамов Собиржон Аълаевич; Абсаломова Мадинахон Хайрулла кизи; Ғайбуллаева Азиза Шавкат қизи; Алманов Абрам Бўрон ўғли (Web of Journals Publishing, 2024)
This article presents the results of studies conducted in the Syrdarya region, which make it possible to reduce the impact of deflation on soils, as well as to observe various deflationary processes on irrigated lands in the region. Based on the results of experiments conducted in the region, it is recommended to sow industrial crops in the range of crops to restore, increase and protect the fertility of deflated soils.
Keywords: Wind erosion, crops, soil fertility, deflation, experimental field